Cognitive dysfunction and cortical structural abnormalities in first-episode drug-naïve schizophrenia patients with auditory verbal hallucination - Shen, Xuran; Jiang, Fuli; Fang, Xinyu; Yan, Wei; Xie, Shiping; Zhang, Rongrong (Frontiers in Psychiatry, 2022)
Objective: The current study aimed to examine the cognitive profiles and cortical structural alterations in first-episode drug-naïve schizophrenia with AVH(auditory verbal hallucination). Methods: Cortical structural parameters including cortical thickness and local gyrification index(LGI) estimated using FreeSurfer as well as cognitive performance assessed on the MATRICS Consensus Cognitive Battery (MCCB) were acquired from 78 schizophrenia patients with AVH, 74 schizophrenia patients without AVH(Non-AVH) and 76 healthy controls(HC). Hoffman Auditory Hallucination Rating Scale(HAHRS) was applied to assess the severity of AVH. Results: The results revealed extensive deficits in all cognitive domains among AVH, Non-AVH and HC groups. Compared to Non-AVH group, the AVH group showed poorer performance on visual learning and verbal learning domains. There were six brain regions with cortical thinning in the right hemisphere of inferior temporal gyrus, superior temporal gyrus, lateral orbito frontal cortex, rostral anterior cingulate cortex, supramarginal gyrus and insula, and two brain regions with increased LGI in the left hemisphere of superior parietal gyrus and the right hemisphere of caudal anterior cingulate cortex on AVH group relative to Non-AVH group. Correlation analysis revealed that the cortical thickness in the right hemisphere of lateral orbito frontal cortex was negatively correlated with the severity of AVH in schizophrenia patients with AVH. Conclusions: Visual learning, verbal learning dysfunction and specific disruption of cortical structure may be the therapeutic targets for clinical interventions in AVH when addressing cognitive dysfunction and AVH, while the pathological mechanisms underlying cognition and AVH warrant further investigation.